PENINGKATAN DAYA SAING USAHA MIKRO ANGGOTA PPKM KABUPATEN BANDUNG MENGGUNAKAN MODUL SCORE ILO - Mulia, Fernando; Marlencia, Cerry (Universitas katolik Musi Charitas, 2021)
Competition nowadays requires companies to continuously anticipate by adapting with changes in the business environment. When a company unable to adjust, there is a possibility that the company will be less competitive than other companies. Changes in political, economic, social, cultural, and technological conditions are crucial for constant attention. Companies are expected to always respond to changes that occur, including UMKM (MSME). MSMEs in Bandung Regency have an Organization, called “Paguyuban Pengusaha Kecil Menengah (PPKM) Kabupaten Bandung”, West Java, which has members with various types of businesses. Based on the results of interviews with the staff of the Cooperatives and SMEs Service and the Chairman of the UMKM Association of Bandung Regency, the problems that often occur in the UMKM environment there are quite diverse, such as problems in the production process, quality of goods, marketing, financial records, which lead to low competitiveness. Sustaining Competitive and Responsible Enterprises (SCORE) program from the International Labour Organization (ILO) is a program that aims to increase productivity, cooperation, and workers' commitment to the company. This program will increase competitiveness, starting with improvements in the internal company. The UNPAR SCORE program which was held in 2020 is the 4th batch and in its implementation experienced the COVID19 Pandemic, so it was forced to undergo various adjustments. There were several conditions that caused some participants not to survive, but out of 33 participants, 20 MSMEs completed the SCORE UNPAR Batch 4 program until the final presentation. Keywords: Competitiveness, MSME, SCORE